Evaluation of a Marker Clip System in Sonographically Guided Core Needle Biopsy for Breast Cancer Localization Before and After Neoadjuvant Chemotherapy - Schulz-Wendtland, Rüdiger; Dankerl, P.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Schrauder, M. G.; Beckmann, Matthias; Uder, M.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Introduction The placement of intramammary marker clips has proven to be helpful for tumor localization in patients undergoing neoadjuvant chemotherapy and breast-conserving surgery. The purpose of our study was to investigate the feasibility of using a clip marker system for breast cancer localization and its influence on the imaging assessment of treatment responses after neoadjuvant chemotherapy. Patients and Methods Between March and June 2015, a total of 25 patients (n = 25), with a suspicion of invasive breast cancer with diameters of at least 2 cm (cT2), underwent preoperative sonographically guided core needle biopsy using a single-use breast biopsy system (HistoCore(TM)) and intramammary clip marking using a directly adapted clip system based on the established O-Twist Marker(TM), before their scheduled preoperative neoadjuvant chemotherapy. Localization of the intramammary marker clip was controlled by sonography and digital breast tomosynthesis. Results Sonography detected no dislocation of intrammammary marker clips in 20 of 25 patients (80 %), while digital breast tomosynthesis showed accurate placement without dislocation in 24 patients (96 %) (p < 0.05). There was no evidence of significant clip migration during preoperative follow-up imaging after neoadjuvant chemotherapy. No complication related to the clip marking was noted and there was no difficulty in evaluating the treatment response to neoadjuvant chemotherapy. Among the breast-conserving surgeries performed, no cases were identified in which intraoperative loss of the marker clip had occurred. Conclusion Our study underscores the importance of intramammary marking clip systems before neoadjuvant chemotherapy. Placement of marker clips is advised to facilitate accurate tumor bed localization. With regard to digital breast tomosynthesis, its development continues to improve the quality of diagnostics and the therapy of breast cancer particularly for small breast cancer tumors or in neoadjuvant chemotherapy setting.
EVALuna2:14620